Observation of crystallization of amorphous solid water under the conditions of secondary emission mass spectrometric experiments: Biological Systems at Low Temperatures - Kosevich, M.V.; Boryak, O.A.; Shelkovsky, V.S.; Orlov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A phenomenon of termination of sputtering of protonated water clusters (H2O)nH+ in low-temperature secondary emission mass spectrometric studies of solid water was observed in the temperaturerange of crystallization of amorphous solid water (ASW). In this range the mass spectra contained only H3O+, H2O+•, and OH+ ions. The following explanation of the revealed phenomenon is suggested: the heat supplied to the ASW sample by the bombarding particles is spent on initiation of an amorphous–crystalline transition within the condensed sample but not for the transfer of the sample matter to the gas phase. At the same time heat released on crystallization causes a local rise in temperature of the crystallizing sample surface, which enhances the rate of sublimation of ice. The resulting increased concentration of subliming water molecules over the sample surfaceis reflected in the growth of abundance of H2O+• molecular ion-radical, produced by gas-phase ionization mechanism. The appearance of a set of low-mass peaks in the course of crystallization observedfor some types of ASW samples is explained by the release of gases trapped in the ASW film during its growth.